Lower Urinary Tract Symptoms as Diagnostic Clues in Parkinsonism: A Practical Framework for Neurologists - Saar Anis; Omer Anis; Abhishek Lenka; Junaid H. Siddiqui (Movement Disorders Clinical Practice, 2026)
Abstract Background Lower urinary tract symptoms (LUTS) are among the most prevalent nonmotor complaints across the parkinsonian spectrum, yet they remain underutilized as diagnostic and management signals in neurology practice. Although prior reviews have characterized disease‐specific patterns of urinary dysfunction, and recent guidelines address neurogenic LUTS broadly, no prior framework has explicitly focused on how the practicing neurologist can interpret LUTS as part of the diagnostic workup and integrate them into disease‐specific management across parkinsonian disorders. Methods The aim of the review was to provide a neurology‐centered narrative review reframing LUTS as diagnostic clues in parkinsonism and to propose a practical clinical evaluation framework for neurologists. We conducted a narrative review of published literature on LUTS across parkinsonian disorders, identified through PubMed/MEDLINE searches through March 2026, supplemented by manual review of reference lists and relevant guidelines. Results Disease‐specific LUTS patterns can carry diagnostic relevance that can inform the neurologic differential diagnosis. Early urinary retention or elevated postvoid residual volume should raise suspicion for multiple system atrophy. Nocturia in Parkinson's disease is frequently multifactorial, requiring stepwise evaluation of dopaminergic timing, sleep disorders, nocturnal polyuria, and fluid shifts before bladder‐directed therapy is initiated. LUTS may interact with mobility and falls through urgency‐freezing convergence and nocturia‐orthostatic hypotension overlap. Antimuscarinic agents carry compounded risks of cognitive impairment, delirium, and falls in this population. Conclusions A pragmatic framework using symptom classification, postvoid residual measurement, red flag identification, and targeted pharmacologic guidance can support safe and timely LUTS management within routine neurology practice.